2013
DOI: 10.1002/ppul.22738
|View full text |Cite
|
Sign up to set email alerts
|

An infant with pulmonary interstitial glycogenosis: Clinical improvement is associated with improvement in the pulmonary diffusion capacity

Abstract: Pulmonary interstitial glycogenosis (PIG) is an idiopathic interstitial lung disease of infants. The underlying pulmonary pathophysiology of PIG has not been well characterized. Herein we report a term-gestation infant who presented with persistent tachypnea and hypoxia. A chest CT scan demonstrated a diffuse ground glass appearance and lung biopsy demonstrated increased alveolar septae cellularity with glycogen-containing cells, consistent with a diagnosis of PIG. At 3 months of age, pulmonary function testin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
12
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 9 publications
1
12
0
Order By: Relevance
“…Sometimes ground-glass opacities are absent or have a different distribution (3,6,7,21). With regard to biopsy-proven PIG, the few published CT studies have shown mainly ground-glass opacities in a subsegmental, segmental, or diffuse distribution (11,15), very similar to what was found in NEHI (11): interlobar septal thickening or scarring, hyperinflation, air trapping, multifocal atelectasis (7), and multiple air-filled cystic changes of variable size (12).…”
supporting
confidence: 49%
See 1 more Smart Citation
“…Sometimes ground-glass opacities are absent or have a different distribution (3,6,7,21). With regard to biopsy-proven PIG, the few published CT studies have shown mainly ground-glass opacities in a subsegmental, segmental, or diffuse distribution (11,15), very similar to what was found in NEHI (11): interlobar septal thickening or scarring, hyperinflation, air trapping, multifocal atelectasis (7), and multiple air-filled cystic changes of variable size (12).…”
supporting
confidence: 49%
“…Histological examinations show oval, glycogen-rich mesenchymal cells expanding the interstitium. No fibrosis or inflammatory reaction is seen (11)(12)(13)(14)(15)(16)(17)(18)(19)(20). Of interest, NECs are also hyperplastic (10).…”
mentioning
confidence: 99%
“…6 Outcomes have overall been favorable, but few data on long term follow-up exist, with the longest being 6 years. 2,4,8 …”
Section: Introductionmentioning
confidence: 99%
“…Pulmonary function testing reveals a restrictive lung disease with marked reduction of pulmonary diffusing capacity. The observations that resolution of PIG on histology and improvement in pulmonary diffusion capacity and forced vital capacity coincide with clinical improvement suggest that PIG impairs respiratory function via alveolar septal thickening (Ehsan et al 2014), although the ultimate clinical outcome primarily depends upon the severity of any underlying lung growth abnormality (King et al 2011), and no mortality is associated with cases of isolated PIG. Corticosteroid therapy may hasten the resolution of PIG, possibly due to acceleration of lung maturation rather than to suppression of inflammation (Deterding 2010;Deutsch and Young 2010;Canakis et al 2002;Onland et al 2005), but should be used judiciously in this self-limited disorder due to the risks of neuro-developmental impairment, immunosuppression, and poor wound healing associated with corticosteroids (Radman et al 2013).…”
Section: 3mentioning
confidence: 99%